Fiberoptic Bronchoscopy Versus Video Laryngoscopy in Pediatric Airway Management - Marijana Karišik; Dušanka Janjević; Massimiliano Sorbello (Acta Clinica Croatica, 2016)
The primary goal of pediatric airway management is to ensure oxygenation and ventilation. Routine airway management in healthy pediatric patients is normally easy in experienced hands. Really difficult pediatric airway is rare and usually is associated with anatomically and physiologically important findings such as congenital abnormalities and syndromes, trauma, infection, swelling and burns. Using predictors of difficult intubation should be mandatory preoperative assessment in pediatric patients. Difficult airway algorithm for pediatric patients has to consist of three parts: oxygenation (A), tracheal intubation (B), and rescue (C). According to this new algorithm, if conventional direct laryngoscopy fails, we have to use alternative glottic visualization device. Do we really need video laryngoscopy? If we look at numbers, we might estimate that conventional laryngoscopy is successful and effective in around 98.5% of cases. Do we need to replace Macintosh laryngoscope with video laryngoscope completely in our routine practice? Should video laryngoscope be available to replace fiberoptic intubation in pediatric airway management? According to the algorithm, fiberoptic-assisted tracheal intubation combined with extraglottic airway devices is the standard of care. Establishment of protocols for equipping and maintaining airway trolleys and regular training in their use must be provided to avoid tissue hypoxia in children with compromised airway.